Ammonia, hydrogen sulfide, methane and carbon monoxide in swine production - Sampaio, Carlos Augusto de Paiva; Nääs, Irenilza de Alencar; Salgado, Douglas D’alessandro (Revista de Ciências Agroveterinárias, 2006)
Information about gases concentrations and their effects on animal and human’s welfare in swine confinement production systems are scarce in Brazil. The objectives of this research were to evaluate the air quality (NH3, H2S, CH4 and CO) and to estimate the worker occupational risk exposition at growing and finishing commercial swine production facilities. The results showed that average concentrations of H2S, CO and CH4 were lower than 1 ppm, smaller than 1 ppm, and lower than 0.1% by volume, respectively. Such concentration levels are not dangerous to animals and workers health according to the recommended norms. The average concentration of NH3 was significantly affected (P < 0.05) by the feeding schedule, installation type and evaluated period.